Historians on the Homefront : American Propagandists for the Great War - Blakey, George T. (Book collections on Project MUSE., 1970)
When Woodrow Wilson called on the American people to mobilize for war in April 1917, it was hardly surprising that historians should respond to their one-time colleague. Mobilization produced three organizations staffed by many of America's leading historians. All three organizations, the author shows, viewed as their task the mobilizing of America's intellectual resources in support of Wilson's war policies. The postwar decade saw an inevitable cooling of wartime passions and a reevaluation of the causes of the war. George T. Blakey examines the postwar reaction to the activities of the CPI, NBHS, and NSL, which included congressional investigations and acerbic attacks in popular and scholarly periodicals. A number of the historians came to regret their wartime propaganda work; a few of these joined the ranks of the revisionists and turned on their colleagues. Others merely strengthened their Germanophobia. The majority, Mr. Blakely finds, resumed their academic careers, apparently untouched by the part they had played in mobilizing the American war effort. The question of scholarly integrity versus propaganda has never been fully resolved, the author concludes, but later generations of historians can still learn much from the example of America's World War I historians-turned-propagandists.